The Avant-Gardist, the Male Genius and the Proprietor - Fredriksson, Martin (Nordlit, 2007)
As the title suggests, this article will deal not only with the avant-garde and the romantic idea of geniality but also with the much more mundane concept of literary property. Even though the law might seem alien to the lofty ideals of the avant-garde artist, the construction of the creative genius and the birth of copyright will eventually prove to be quite closely connected. But before I move on to the legal part I would like to start with the essentials: with the author, or the artist. The American artist John de Andreas sculpture The Artist and his model from 1980 is probably one of the most revealing pictures of the avant-gardist selfconception ever made. This is a picture of the artist at work, but I will argue it can also be regarded as a legal character. What meets the eye is however very far from the law as we know it. de Andreas sculpture is a self-portrait of the artist at work: a highly naturalistic full-scale portrait of two people. One of them is a naked woman, resting casually on a white socket and looking down on the other who is a fully dressed man. As the title clearly states, the sculpture depicts the classical relation between The Artist and his Model, and it is no coincidence that the artist has a male pronoun and the model a female body. The roles of the artist and his model are traditional stereotypes which we can find in most books on art history - one is an artist and the other is a model; one is a man and the other is a woman; one is dressed and the other one is undressed.